(x)(x+1)=323

Simple and best practice solution for (x)(x+1)=323 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x)(x+1)=323 equation:



(x)(x+1)=323
We move all terms to the left:
(x)(x+1)-(323)=0
We multiply parentheses
x^2+x-323=0
a = 1; b = 1; c = -323;
Δ = b2-4ac
Δ = 12-4·1·(-323)
Δ = 1293
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(1)-\sqrt{1293}}{2*1}=\frac{-1-\sqrt{1293}}{2} $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(1)+\sqrt{1293}}{2*1}=\frac{-1+\sqrt{1293}}{2} $

See similar equations:

| -21=7x-5(2x+9) | | 6-5v=41 | | 2(m+1)-6m=6 | | 9s^2-18s+9=0 | | x10+15=320 | | 9d+7dd=5 | | 38=-4+7r | | 3(x+2)-8=24 | | n+11/10=82/5 | | G(x)=2|x+3|-4 | | 7v=3v-12 | | 6x^-2x=20 | | -3/5b=9 | | 4y-3-y+8=11y | | 8x+9=-8x-5 | | (25x)+(22x+9)=180 | | b+14/18=4 | | X-2x7=-7 | | 4a+2.1=2.7 | | 3(3+x)=2(x+3) | | w/4+7=10 | | 5x+11-4x=18 | | 7d-2=4(d=1) | | 5/6x-2=4 | | 3x-9=-3(x+11) | | 19c+19=19 | | 8y-4y-6=67.84 | | n=-16 | | 2(x+8)=2x+-8 | | 7-2x=2(x-4)-4 | | 2(x+8)=2x+-16 | | 13x-21=19x+3 |

Equations solver categories